Pengaruh Female Ceo, Information Asymmetry, Dan Leverage Terhadap Earning Management - Evelina Sofia, Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to obtain information by conducting empirical testing on the influence of female CEO independent variables, Information asymmetry, and leverage on independent earnings management variables in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018 period. In this study there were 59 manufacturing companies selected and used as samples by using purposive sampling as a sampling technique and testing multiple linear regression analysis. This study explains the results of testing on the variable Female CEO and Information Asymmetry with the results that show no significant effect on earnings management while the leverage variable shows a positive and significant relationship to earnings management.